Falling Words and their Connotations in the Holy Qur’an: A Rhetorical Study - Al-Asmari, Misfer Bin Muhammad (Arts for Linguistic & Literary Studies, 2023)
This research explores the terminology used in the Holy Quran to convey the concept of 'falling'. It conducts a rhetorical-linguistic analysis to identify the semantic distinctions among these terms and highlights the Quranic rhetoric involved in selecting the most precise word to convey the intended meaning. The study is divided into two sections: one focusing on words indicating a general sense of falling, and the other addressing expressions that indicate a specific meaning of falling. The preface discusses the interest of linguists in examining semantic differences between synonymous words, the significance of linguistic variances in rhetorical analysis, and the Quran's eloquence in choosing appropriate words to convey precise meanings. The research findings demonstrate that there exists a relationship between the words denoting falling, both in a general and specific sense. While all of these terms are used in the Quran to convey the notion of falling and dropping, each term possesses unique connotations that differentiate it from the others. This illustrates the Quran's eloquence in utilizing the most suitable word in its given context. Some terms are used literally, such as "fell," "descended," and "landed," while others are used metaphorically, such as "slipped" or "fell down in fear of Allah."